Bioactivity Guided Fractionation And Antioxidant Evaluation. - Lee, Tze Jiun; Sulaiman, Shaida Fariza (2004)
The leaves of Mimosa pigra were extracted by boiling in 80%o methanol. The FTC(Ferric thiocyanate) and TBA (Thiobarbituric acid) methods were used to determine the antioxidant activities.2,6-ditert-butylphenol 99.0% (BHT) and a-tocopherol were used as positive controls.